2010
DOI: 10.1002/jmr.1022
|View full text |Cite
|
Sign up to set email alerts
|

Metal dependent hydrolysis of β-casein by sIgA antibodies from human milk

Abstract: We present the first evidence that electrophoretically and immunologically homogeneous sIgAs purified from milk of healthy human mothers by chromatography on Protein A-Sepharose and FPLC gel filtration contain intrinsically bound metal ions (Ca > Mg ≥ Al > Fe approximately  Zn ≥ Ni ≥ Cu ≥ Mn), the removal of which by a dialysis against ethylenediamine tetraacetic acid (EDTA) leads to a significant decrease in the β-casein-hydrolyzing activity of these antibodies (Abs). An affinity chromatography of total sIgAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 44 publications
3
33
0
Order By: Relevance
“…Protease IgGs from the sera of ~95-100% of patients with different autoimmune pathologies [9,66,116], human milk Abs hydrolyzing casein [96,117], Abs from AIDS patients hydrolyzing HSA, casein, and HIV reverse transcriptase [95] are serine-like proteases, whose activity is strongly decreased after their preincubation with serine protease-specific inhibitors PMSF. In addition, a high metal-dependent MBP-hydrolyzing activity for MS IgGs [86] and caseinhydrolyzing of human milk sIgAs [96] were recently revealed.…”
Section: Lupus 70mentioning
confidence: 99%
See 1 more Smart Citation
“…Protease IgGs from the sera of ~95-100% of patients with different autoimmune pathologies [9,66,116], human milk Abs hydrolyzing casein [96,117], Abs from AIDS patients hydrolyzing HSA, casein, and HIV reverse transcriptase [95] are serine-like proteases, whose activity is strongly decreased after their preincubation with serine protease-specific inhibitors PMSF. In addition, a high metal-dependent MBP-hydrolyzing activity for MS IgGs [86] and caseinhydrolyzing of human milk sIgAs [96] were recently revealed.…”
Section: Lupus 70mentioning
confidence: 99%
“…In addition, a high metal-dependent MBP-hydrolyzing activity for MS IgGs [86] and caseinhydrolyzing of human milk sIgAs [96] were recently revealed. It was shown that antiintegrase IgGs and IgMs of HIV-infected patients can contain abzymes hydrolyzing viral integrase of four types, resembling serine, thiol, metal-dependent, and acidic proteases, the ratio of which may be individual for every AIDS patient [97,98].…”
Section: Lupus 70mentioning
confidence: 99%
“…We have analyzed the type of proteolytic activity of AIDS pIgGs and pIgMs in the hydrolysis of IN and -casein. It was shown, that in contrast to milk sIgAs 2011) and similarly to several other proteolytic Abzs, only specific inhibitor of serine protease AEBSF significantly suppress AIDS pIgG-dependent hydrolysis of -casein, while EDTA has no significant effect. We have analyzed the type of IN-hydrolyzing activity of ten AIDS pIgGs; several typical examples are given in Fig.…”
Section: Structural Diversity Of Aids Abzymesmentioning
confidence: 97%
“…Proteolytic IgGs from the sera of patients with asthma hydrolyzing VIP (Paul et al, 1989), Hashimoto thyroiditis and rheumatoid arthritis hydrolyzing thyroglobulin (Li eta l., 1995;Kalaga et al, 1995) are serine-like proteases, and their activity is most strongly reduced after incubation with specific serine protease inhibitors PMSF or AEBSF. It was shown that casein-hydrolyzing sIgAs from human milk 2011) and hMBP-hydrolyzing IgGs and IgMs from the sera of patients with MS (Polosukhina et al, 2004(Polosukhina et al, , 2005(Polosukhina et al, , 2006 contain not only Ab subfractions with serine-like, but also specific subfractions with metal-dependent activity. We have analyzed the type of proteolytic activity of AIDS pIgGs and pIgMs in the hydrolysis of IN and -casein.…”
Section: Structural Diversity Of Aids Abzymesmentioning
confidence: 99%
See 1 more Smart Citation